1997
DOI: 10.3109/17518429709167353
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of strength training in prepubescent to early postpubescent males and females: Effects of gender and maturity

Abstract: There has been considerable debate concerning the benefits of children participating in weight training programs. With the potential benefits of such training in specific rehabilitation regimens, the safety/efficacy of weight training is a topic in need of scientific study. Fifty-two experimental and 39 control subjects participated in this study. A 2 x 2 x 2 (gender by treatment by Tanner stage) ANOVA was used to examine pre- to post-test differences in six strength measures, eight anthropometric measures, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
82
1
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 15 publications
9
82
1
6
Order By: Relevance
“…PHV timing, rate, and magnitude are not impacted by regular physical training or sports participation, as demonstrated by several research studies (4,8,11,14,15,18,19,56). However, regular weight training may positively change the FM/FFM ratio and contribute to increase FFM.…”
Section: Growth Development and Trainingmentioning
confidence: 77%
See 2 more Smart Citations
“…PHV timing, rate, and magnitude are not impacted by regular physical training or sports participation, as demonstrated by several research studies (4,8,11,14,15,18,19,56). However, regular weight training may positively change the FM/FFM ratio and contribute to increase FFM.…”
Section: Growth Development and Trainingmentioning
confidence: 77%
“…However, muscle mass growth may be relatively more pronounced among males due to the greater androgenic effects. Female adolescents reach a plateau of muscle strength increases by about age 15 years (2,4,15,19), while males demonstrate an acceleration of muscle strength around age 13 years. The peak increase in muscle strength follows a peak in muscle mass by about 12 months (2,8,15).…”
Section: Muscle Growth and Strengthmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Although the capability of children to increase their muscular strength was questioned in the past, 4 current findings suggest that children may benefit from regular participation in resistance training activities. Reports indicate that youth resistance training may improve motor performance skills, 5 may reduce injuries in sports and recreational activities, 6,7 and may favorably alter selected anatomic 8 and psychosocial parameters. 9,10 The American Academy of Pediatrics, 11 the American College of Sports Medicine, 12 and the National Strength and Conditioning Association 1 support children's participation in appropriately designed and competently supervised resistance training programs.…”
mentioning
confidence: 99%
“…The training programs for this study were based on available data sources [4,11,13,24,25] that used both children and adolescents who were either non-athletes or athletes. As our resistance training programs were predominantly designed to evaluate how young Thai male athletes respond to the program, subjective information revealed that young Thai male athletes were highly capable of performing all exercise routines throughout the two weeks of study.…”
Section: Discussionmentioning
confidence: 99%